(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The goal of this article is to provide more context for the work being done by the NationalElectronic Pharmacy Platform (NEPP) to increase awareness of and access to virtual drugstores in SaudiArabia. A quantitative cross-sectional analysis was conducted using data from 80 of the 220 onlinepharmacies registered with the NEPP. A comprehensive statistical profile of evolving patterns ofpharmaceutical usage in Saudi Arabia was compiled using numerical analysis of the data. Even if NEPPdidn’t become widely available until 2023, there’s certainly growing interest among pharmacists. There isa great deal of space for growth, and maintaining efforts to spread awareness and educate people isessential to its continuation. The relevance of the NEPP model for the different African countries ishighlighted by the rising interest in pharmacy regulation and the growth of online drugstores. Thepotential future effects of NEPP on Saudi Arabia’s healthcare system are highlighted by this study. Ansignificant result is the rising prevalence of prescriptions for antibacterial medicines. This might indicatea rise in bacterial infections, particularly those affecting respiratory function, among the Saudi populace.Treating these infections and increasing understanding of antibacterial-related diseases are also vital.Our results may be useful to the Ministry of Health, the Saudi Health Service, and the Pharmacy Councilas they develop plans to address health problems caused by antibiotic resistance.